127 Multidisciplinary management of a complex course of methylmalonic aciduria. (December 2018) - Forny, P; Munir, S; Stojanovic, J; Hadzic, N; Barone, G; Vara, R; Gruenewald, S
Abstract : We present a particularly complex case of a patient with the underlying condition methylmalonic aciduria (MMA) – an inborn error of protein metabolism, which is characterized by the accumulation of methylmalonic acid in tissues and body fluids. The index case of the family (elder sibling) is also affected by mut 0 MMA (homozygous mutation in the MUT gene c.692dup). At 5 years he has a stable course, had only minor metabolic decompensations, but is autistic and has learning difficulties. The younger sibling turned out to be a rather complex case, only diagnosed postnatally as parents declined prenatal genetic testing. However, on antenatal organ scan he was diagnosed with multicystic dysplastic kidneys which caused problematic fluid losses soon after birth. He was prospectively treated as possible MMA and the diagnosis was confirmed genetically soon after birth. He also had raised methylmalonic acid in urine and plasma and hyperammonaemia. During routine monitoring, high gamma-glutamyl transferase levels up to 1212 U/L (reference 30–177) triggered a detailed investigation of the liver, which revealed a heterogenous, hyperechoic lesion on ultrasound and significantly increased alpha-fetoprotein levels at 19.653 ng/mL (0–10), whereupon hepatoblastoma was confirmed on liver biopsy. Liver transplantation is considered in severe MMA cases to avoid frequent decompensations and non-neurological long-term complications. After a multidisciplinary assessment, liver transplant was performed, serving the dual purpose of removal of the tumour as well as supportive treatment for the underlying MMA. Perioperatively and following post-transplant chemotherapy, the patient showed good metabolic control throughout. This report shows two siblings with the same genetic metabolic diagnosis but completely different courses, as unexpected symptoms, such as hepatoblastoma and dysplastic kidneys in this case, are present, leading to different treatment strategies. To which extent the development of the liver tumour might be fostered by the underlying MMA disease, needs to be further studied in the future.